Creating the BELgian COngenital heart disease database combining administrative and clinical data (BELCODAC): Rationale, design and methodology. (1st October 2020) - Ombelet, Fouke; Goossens, Eva; Willems, Ruben; Annemans, Lieven; Budts, Werner; De Backer, Julie; De Groote, Katya; Moniotte, Stéphane; Van Bulck, Liesbet; Marelli, Ariane; Moons, Philip; ,
Abstract: Background: Congenital heart disease (CHD) entails a broad spectrum of malformations with various degrees of severity and prognosis. Consequently, new and specific healthcare needs are emerging, requiring responsive healthcare provision. Research on this matter is predominantly performed on population-based databases, to inform clinicians, researchers and policy-makers on health outcomes and economic burden of CHD. Most databases contain data either from administrative sources or from clinical systems. We describe the methodological design of the BELgian COngenital Heart Disease Database combining Administrative and Clinical data (BELCODAC), to investigate patients with CHD. Methods: Data on clinical characteristics from three university hospitals in Belgium (Leuven, Ghent and Brussels) were merged with mortality and socio-economic data from the official Belgian statistical office (StatBel), and with healthcare use data from the InterMutualistic Agency, an overarching national organization that collects data from the seven sickness funds for all Belgian citizens. Over 60 variables with multiple entries over time are included in the database. Results: BELCODAC contains data on 18, 510 patients, of which 8926 patients (48%) have a mild, 7490 (41%) a moderately complex and 2094 (11%) a complex anatomical heart defect. The most prevalent diagnosis is Ventricular Septal Defect in 3879 patients (21%), followed by Atrial Septal Defect in 2565 patients (14%). Conclusions: BELCODAC comprises longitudinal data on patients with CHD in Belgium. This will help build evidence-based provision of care to the changing CHD population. Highlights: BELCODAC includes clinical data on healthcare use and outcomes in patients with CHD. It is an alliance between universities, hospitals and governmental organizations. BELCODAC comprises longitudinal data on 18, 510 patients with CHD in Belgium. It will enable research on outcomes and economic burden of healthcare use in CHD.